Oral health in renal transplant recipients administered cyclosporin A or tacrolimus - Spolidório, Luis Carlos [UNESP]; Spolidório, Denise Madalena Palomari [UNESP]; Massucato, Elaine Maria Sgavioli [UNESP]; Neppelenbroek, K. H.; Campanha, N. H.; Sanches, M. H. (Blackwell Publishing, 2006)
OBJECTIVE: the aim of this study was to determine the oral status of renal transplant recipients receiving cyclosporin A (CsA) or tacrolimus (FK-506) as immunosuppressant.SUBJECTS AND METHODS: A total of 88 renal transplant recipients receiving CsA (63 men and 25 women, mean age 51.4 years) and 67 receiving FK-506 (57 men and 10 women, mean age 33.5 years) were included in the study. Donor type, histocompatibility, cold ischemia time and prior delayed graft function were similar between the two groups. Demographics and pharmacological data were recorded for all subjects.RESULTS: the results demonstrated that CsA caused a greater number of oral diseases. A greater number of gingival overgrowth was present in patients treated with CsA. However, the combined use with calcium channel blockers increased the gingival overgrowth number. The occurrence of candida in saliva was observed in 80 renal recipients treated with CsA and 20 treated with FK-506. The presence of squamous oral carcinoma (n = 3) and herpes simplex (n = 10) was observed in patients treated with CsA. These alterations were not observed in renal recipients treated with FK-506.CONCLUSIONS: Renal recipients constitute a high-risk group for oral diseases, as they are immunocompromised. However, the FK-506 regime appears to ameliorate this effect, compared with CsA. Adequate pre- and post-transplant oral health care is recommended for these subjects, irrespective of the time interval for which the drug is administered.
Keywords: oral health; renal transplant; cyclosporin; tacrolimus